Registros numéricos de crianças do 2º ano do ensino fundamental: diversidade e relações - Dias, Sandra Maria Soeiro (2015)
The Decimal Numbering System – DNS is an essential mathematical knowledge at the beginning of Basic Education, which student requires the ability to read and write numerals using various types of records – pictorial, with objects, with digits, with letters – as explained by theory of Semiotics Representation Registers. It must be noted also the importance of oral communication – listening and speaking – in all subject learning processes. This research, qualitative, held in a public school in the municipality of Caucaia, aimed to: i) identify the relationship between the diversity of numerical records of children in the 2nd year of elementary school; ii) know the students representative records of the 2nd year of elementary school writing numbers with 2, 3 and 4 orders; and iii) interpret the students with knowledge of numerical records 2, 3 and 4 orders. Two instruments were applied: the Instrument 1 had numerals 2 and 3 orders and the Instrument 2 had numerals with four orders. The participants were 14 students of 2nd year of elementary school, who had their knowledge analyzed by different types, listed by Barguil (2015), and in the light of the theory of Numerical Transcoding (OROZCO, 2005), which classifies errors as syntactic or lexicon. The questions were about the comparison of numerals and the record numbers, with digits and letters, noting the relationship of this with orality. Data analysis was organized in two stages: i) performance of students in each issue; and ii) the overall performance of each student in all matters. The results revealed a significant amount of syntactical errors, which are referred to in verbal expression, as well as indicate the orality as the main starting point for the correct construction of these records, which indicate the need to expand the use of records of diversity for learning DNS.